Issues of Education and Training in Music Culture Lessons (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
The importance of music culture lessons in educational systems cannot be overstated. They play a crucial role in shaping students' aesthetic values, fostering emotional expression, and cultivating a deeper understanding of cultural heritage. The primary purpose of these lessons is to educate students not only in musical techniques and theory but also in cultural identity and emotional intelligence. This paper explores the issues surrounding education and training within music culture lessons, focusing on their role in nurturing a well-rounded student, promoting aesthetic education, and preserving cultural heritage. The study examines teaching strategies, challenges, and the significance of integrating music culture into broader educational curricula. Additionally, it emphasizes the role of music in fostering discipline, creativity, and community involvement. By exploring these facets, this paper provides a comprehensive look at the educational and moral aspects of teaching music culture.